Interações profissionais de saúde e mães de prematuros: impacto na maternagem - Custodio, Natalia (Universidade Federal de São Carlos, 2014)
The present study aimed to understand the interactions between the mother and health professionals from the time of the birth of her preterm child until the first month after hospital discharge (interfere / affect) and their influence on the development of maternal care, the other aim was to identify the social network of these women that was significantly important in this process with attention to the position of health professionals. This was a qualitative study, which adopted the theoretical reference of Symbolic Interactionism and the methodological reference of Interpretive Interactionism. For data collection, an ecomap was constructed and a semistructured interview was conducted. Eight mothers who experienced the hospitalization of a child in the Neonatal Intensive Care Unit and were in the period of up to one month post-hospital discharge participated in the study. Data analysis enabled the extraction of the social support network for these women, when two situations were identified: participation and nonparticipation of the father. Further, it is in REVIEWING THE DEPENDENCE OF THE PROFESSIONAL AND HIS COMPETENCE FOR CARE that the woman manages to evolve care together with her child in an autonomous manner. The unveiled categories were: believing and obedient relationship; insecure and questioning relationship; and, reflective and emancipatory relationship. The results show that the interaction between mothers and professionals is grounded in power and this factor affects the mother's trajectory while assuming the maternal role. Thus, it is essential to provide welcoming and support in a humane manner, considering the precepts of family-centered care. We hope that this study contributes to health professionals from Neonatal Intensive Care Units with regard to the review of care provided to mothers/family.
Interactions of health professionals and mothers of premature infants: impact on motherhood
Keywords: Prematuros; Relação profissional-família; Alta do paciente; Família; Patient discharge; Family; Premature infant; Professional-family relationships; CIENCIAS DA SAUDE::ENFERMAGEM